PRA PERANCANGAN PABRIK NATRIUM KARBONAT DARI LIMBAH FLUE GAS PLTU DENGAN METODE KARBONASI BERKAPASITAS 350.000 TON/TAHUN - Purwaningsih, Dian Yanuarita (Institut Teknologi Adhi Tama Surabaya, 2025)
Sodium carbonate, commonly known as soda ash, is a chemical compound with the formula Na₂CO₃. It plays a vital role in various industries as a pH regulator in chemical processes, an electrolyte in reactions, and a fluxing agent to lower the melting point in glass production. Despite its wide industrial use, Indonesia currently has no domestic sodium carbonate production facilities, resulting in a growing dependence on imports to meet increasing demand. This preliminary plant design proposes the production of sodium carbonate using the carbonation method, with sodium hydroxide and flue gas waste from coal-fired power plant as raw materials. The process involves reacting NaOH with CO₂ extracted from flue gas in a reactor to form sodium carbonate. The product is then concentrated through evaporation, crystallized into wet crystals, and dried using a rotary dryer. The final stage involves adjusting particle size to meet market specifications for the Na₂CO₃ product. Economic analysis indicates that the plant is financially viable, with an Internal Rate of Return (IRR) of 23%, a Pay Out Time (POT) of 3.8 years, and a Break Even Point (BEP) of 27.28%. In conclusion, establishing a sodium carbonate plant using flue gas waste from the coal-fired power plant with a production capacity of 350,000 tons per year is considered economically feasible.